2018
DOI: 10.3354/esr00892
|View full text |Cite
|
Sign up to set email alerts
|

Physiological stress in the smalltooth sawfish: effects of ontogeny, capture method, and habitat quality

Abstract: Similar to other elasmobranchs, the smalltooth sawfish Pristis pectinata is slow growing, matures late in life, and produces relatively few young, all factors that have contributed to its sensitivity to dramatic population declines from overfishing and habitat loss. Currently, the physiological stress response of these fish to capture or to other physiological challenges such as habitat loss, climatic changes, or pollution is unknown. In the absence of these data, conservation plans may be less effective, maki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 58 publications
0
18
0
Order By: Relevance
“…Reducing the threat of injury and mortality from fisheries remains a top priority for recovering the smalltooth sawfish. Prohaska et al (2018) showed that the species is physiologically resilient and appears capable of surviving capture. Therefore, continuing to educate anglers about the presence of smalltooth sawfish and how to properly release them is essential for recovery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Reducing the threat of injury and mortality from fisheries remains a top priority for recovering the smalltooth sawfish. Prohaska et al (2018) showed that the species is physiologically resilient and appears capable of surviving capture. Therefore, continuing to educate anglers about the presence of smalltooth sawfish and how to properly release them is essential for recovery.…”
Section: Discussionmentioning
confidence: 99%
“…data). Based on the live release of large sawfish from longline gear, it is expected that sawfish are more resilient to capture on this gear in comparison to trawls and gill nets (Prohaska et al 2018, Poulakis & Grubbs 2019, both this Theme Section). Further, lactate and HCO 3 blood levels of animals captured on longlines during permitted field activities indicate that the smalltooth sawfish is a relatively low stress species compared to other elasmobranchs (Prohaska et al 2018).…”
Section: Commercial and Recreational Fisheriesmentioning
confidence: 99%
See 1 more Smart Citation
“…Interdisciplinary, collaborative, habitat-use studies and detailed biological and ecological questions have been answered as part of research published in this Theme Section as a result of long-term surveys conducted within nurseries, especially regarding the smalltooth sawfish (Feldheim et al 2017, Huston et al 2017, Bakenhaster et al 2018, Hollensead et al 2018, Prohaska et al 2018. In addition to identifying geographic regions in which nurseries still exist, near-real-time, fisher-derived data have also been used to maximize tagging efforts, because juveniles exhibit high degrees of site fidelity.…”
Section: Local Ecological Knowledge and Identification Of Nurseriesmentioning
confidence: 99%
“…In the USA and Australia, sawfishes continue to be captured in recreational fisheries, sometimes in large numbers, though the risk of mortality is likely low when they are handled and released properly (Peverell 2005, Waters et al 2014, Prohaska et al 2018. Unfortunately, reports of sawfish being retained or released after the removal of their rostra are still received, even in regions with adequate protections and extensive outreach efforts (Seitz & Poulakis 2006, Morgan et al 2016.…”
Section: Fisheries Catch and Bycatchmentioning
confidence: 99%